Development of a purification strategy for the aqueous phase from biomass pyrolysis - recovery of valuable products - Kick, Christopher; Apfelbacher, A.; Daschner, R.; Hornung, Andreas (European Biomass Conference and Exhibition Proceedings, 2021)
The aqueous phase from biomass pyrolysis is until today mostly seen as worthless by-product and has to be costly disposed. However, it can be a valuable resource for the recovery of products. For this, the composition of the aqueous phase must be known and a suitable purification strategy, adjusted to the pyrolysis feedstock, has to be developed. The aim of this investigation is to introduce a multi-level purification strategy for the aqueous phase gained from the thermo-catalytic reforming of sewage sludge, which allows also the recovery of products. The purification strategy consists out of an electrooxidation step, the decarbonisation of the aqueous phase and the stripping of ammonia by air. By means of this, 44 l hydrogen, 69 g calcium carbonate and 264 g ammonium sulfate can be recovered from 1 l of the aqueous phase. In the medium term, purification strategies like this will lead to a reduction of the overall pyrolysis process costs and decrease the specific costs of targeted pyrolysis products like char, bio oil and syngas.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Ammonia; Biofertilisers; Hydrogen; Innovative concepts; Thermochemical conversion; Wastewater treatment